Implementasi Report Analysis of Preventive Maintenaince (RAOPM) Pada Laboratorium Teknik Mesin Universitas Negeri Makassar - Achmad Romadin; Nurlela Nurlela; Nur Faudah; Ismail Aqsha (Unversitas Negeri Padang, 2024)
The Industrial Revolution has had an impact on the world of vocational education. Practical learning is the main characteristic in answering the challenges of the industrial world. Equipment used in the practicum must have excellent perfomace to be operated. One of the strategies in maintaining equipment in prime condition is the application of the Report Analysis Preventive Maintenance (RAOPM) application. This study aims to monitor the activities of the use of equipment in the laboratory, in order to determine the downtime of the machine. This research uses development research. The results showed that RAOPM in the Makassar State University laboratory has had a tremendous impact on the operational aspects of the laboratory. The implementation of RAOPM from the usage rate indicator, has an average value of 4.21 in the “Very Good” category with a percentage of 52.2%. In terms of maintenance efficiency, it also has a positive impact on knowing machine downtime which can be monitored in real-time. Then the implementation of RAOPM in the laboratory provides various benefits, ranging from increased maintenance efficiency with a predictive approach to better resource management through structured scheduling. RAOPM transforms maintenance from reactive to proactive, lowering breakdown frequency, downtime, and operational costs. In addition, RAOPM improved staff competencies through technology and maintenance management training, fostered a sense of responsibility, and supported the university's sustainability goals by optimizing energy efficiency. Although challenges such as resource limitations and technology adaptation remain, the benefits of RAOPM in improving the university's performance, academic quality, reputation are significant.